Implementation of Syawir Method in Improving Critical Thinking Pattern of Santri in Islamic Boarding School Fathul ‘Ulum Kwagean, Kepung, East Java - Dewi Agus Triani; Mochamad Hermanto (Educan : Jurnal Pendidikan Islam, 2020)
In the 4.0 era the information flow spread so quickly and broadly, on the other side there were many hoaxes circulating in various media, for this reason a critical thinking was needed to filter the information. This study aims to describe the process of implementation of syawir methode, impact, obstacles and as well as to describe the solution of the obstacles in the implementation of syawir methode in forming critical thinking patterns. This research approach is a qualitative study with case study research. The object of this research is santri from Islamic boarding school Fatul ‘Ulum Kwagean Kepung in East Java. Data collection techniques with interviews, observation and documentation. Analysis of the data used in this research is descriptive analysis, with the stages of data reduction, data presentation and drawing conclusions.The results of this research show that: 1) there are two types of syawir, small syawir and large syawir, where the material discussed is subject matter in the Islamic boarding school. 2) there are three impacts namely cognitive impact (understanding and broadening insight) affective (fostering mental self-confidence, tolerance, and critical attitude, as well as respecting the opinions of others), psychomotor impacts (able to describe explanations in a flexible and clear manner and the answer can be justified). 3) There are two obstacles in the implementation of this method, internal factors (lack of self-confidence, different levels of understanding, and lack of concentration) and external factors (lack of time and reference books). 4) Some efforts to be a solution to the obstacles that are, increasing cooperation with the KBM team (Kajian Batsul Masail) to provide guidance and direction on the path of syawir, provide punnish as motivation, add books references, increase duration of time, and directly appoint students who are less active to issue their opinions.